The social integration of a myrmecophilous spider does not depend exclusively on chemical mimicry - Hashim, Rosli; Witte, V.; von Beeren, C. (Springer Verlag, 2012)
Numerous animals have evolved effective mechanisms to integrate into and exploit ant societies. Chemical integration strategies are particularly widespread among ant symbionts (myrmecophiles), probably because social insect nestmate recognition is predominantly mediated by cuticular hydrocarbons (CHCs). The importance of an accurate chemical mimicry of host CHCs for social acceptance recently has been demonstrated in a myrmecophilous silverfish. In the present study, we investigated the role of chemical mimicry in the myrmecophilous spider Gamasomorpha maschwitzi that co-occurs in the same host, Leptogenys distinguenda, as the silverfish. To test whether spiders acquire mimetic CHCs from their host or not, we transferred a stable isotope-labeled hydrocarbon to the cuticle of workers and analyzed the adoption of this label by the spiders. We also isolated spiders from hosts in order to study whether this affects: 1) their chemical host resemblance, and 2) their social integration. If spiders acquired host CHCs, rather than biosynthesizing them, they would be expected to lose these compounds during isolation. Spiders acquired the labeled CHC from their host, suggesting that they also acquire mimetic CHCs, most likely through physical contact. Furthermore, isolated spiders lost considerable quantities of their CHCs, indicating that they do not biosynthesize them. However, spiders remained socially well integrated despite significantly reduced chemical host similarity. We conclude that G. maschwitzi depends less on chemical mimicry to avoid recognition and aggressive rejection than the silverfish previously studied, suggesting that the two myrmecophiles possess different adaptations to achieve social integration.